2020
DOI: 10.1021/acsenergylett.0c01889
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processable Covalent Organic Framework Electrolytes for All-Solid-State Li–Organic Batteries

Abstract: Solid electrolytes (SEs) are milestones in the technology roadmaps for safe and high energy density batteries. The design of organic SEs is challenged by the need to have dynamic structural fluidity for ion motion. The presence of well-ordered one-dimensional (1D) channels and stability against phase transition in covalent organic frameworks (COFs) render them potential candidates for low-temperature SEs. Herein, we demonstrate two milestones using hydrazone COF as an SE: it achieves an ion conductivity of 10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 54 publications
(80 reference statements)
0
141
1
Order By: Relevance
“…When the 2D LiCON is applied in the ASSLB, it is stable for 500 cycles at 500 mA g −1 at 20 °C. [178] In addition, with the unique properties of 2D COF, Sun et al fabricated ultrathin SSEs with a thickness of 7.1 µm, which contributes to the high energy density of the battery. [179] Adv.…”
Section: Other Type Of Solid-state Electrolytesmentioning
confidence: 99%
“…When the 2D LiCON is applied in the ASSLB, it is stable for 500 cycles at 500 mA g −1 at 20 °C. [178] In addition, with the unique properties of 2D COF, Sun et al fabricated ultrathin SSEs with a thickness of 7.1 µm, which contributes to the high energy density of the battery. [179] Adv.…”
Section: Other Type Of Solid-state Electrolytesmentioning
confidence: 99%
“…Recently, Loh et al reported a post-synthetic solution-processable COF stacking approach to significantly mitigate this issue. 86 Another common poly-crystalline defect observed in ordered POPs is crystal cracking. 87 Usually, crystals that grow along the xy-plane often manifest such defects resulting in the creation of added grain boundaries (Fig.…”
Section: Excitons and Charge-carriersmentioning
confidence: 99%
“…The layered conjugated organic solid electrolyte used in lithium/benzoquinone (BQ) secondary batteries showed influentially against the dissolution of BQ and improve cycle stability. [58] The structure of the lithiated covalent organic nanosheet (LiCON-3) was displayed in Figure 5a, its ionic conductivity at 20 °C and À 40 °C were 3.21 × 10 À 5 S cm À 1 and 9 × 10 À 6 S cm À 1 (Figure 5b), respectively. The Li + transference number was 0.92 and the electrochemical stability window was 4.3 V. Assembling the Li/LiCON-3/BQ solid battery and performing 500 cycles at 20 °C with a current density of 500 mA g À 1 (Figure 5c), the capacity remained 87.7 % of its initial specific capacity.…”
Section: Solid Polymer Electrolytesmentioning
confidence: 99%
“…[60,61] For SPEs, replacing the OLEs could Copyright 2020, American Chemical Society. [58] elevate the safety of the batteries. Nevertheless, their room temperature ionic conductivity is generally low and the increase in ionic conductivity is often accompanied by a decrease in mechanical strength.…”
Section: Composite Solid Electrolytesmentioning
confidence: 99%